2020
DOI: 10.1101/2020.09.22.308072
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Higher-order sensorimotor circuit of the brain’s global network supports human consciousness

Abstract: The neural correlates of consciousness, defined as the minimum neuronal mechanisms sufficient for any conscious percept, are usually subject to different interpretations depending on whether one uses measures of local or global brain activities. We argue that the local regions may support consciousness by serving as hubs within the brain's global network. We adopt a unique functional magnetic resonance imaging resting state dataset that encompasses various conscious states, including non-rapid eye movement (NR… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
(70 reference statements)
1
3
0
Order By: Relevance
“…We also found the connections between visual perception and motor regions correlate with the level of consciousness by identifying the importance of the lingual gyrus and supplementary motor area. This supports the theory that the higher-order sensorimotor circuit of the brain network is the infrastructure for consciousness [49].…”
Section: Fc Network With Human Consciousnesssupporting
confidence: 87%
“…We also found the connections between visual perception and motor regions correlate with the level of consciousness by identifying the importance of the lingual gyrus and supplementary motor area. This supports the theory that the higher-order sensorimotor circuit of the brain network is the infrastructure for consciousness [49].…”
Section: Fc Network With Human Consciousnesssupporting
confidence: 87%
“…To dissociate the different involvement of the thalamus-global transient co-activation in arousal and awareness, we recruited two datasets obtained from Zhujiang Hospital (ZJH) and Shanghai Hospital (SHH), which included UWS patients who were considered to have high arousal without awareness ( 1 ). To minimize the effects of structural distortion on the subsequent analysis, we only included the UWS patients with well-preserved brain structures( 7 ). The ZJH and SHH datasets also contained healthy subjects and fully conscious patients with a brain injury (BI) history as control groups (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, a high arousal was marked by eye opening ( 1 ) and higher neural activity of the brain stem ( 2 ). However, despite an extensive research into awareness ( 37 ), there remains a controversy on how specific arousal systems and large-scale brain activity interact in regulating the level of arousal as a component of consciousness.…”
Section: Introductionmentioning
confidence: 99%
“…Qin et al. (2021) demonstrated that the left MTG participated in the formation of a consciousness modulation circuit using an approach that combined degree centrality graph‐theoretical assessment and regions of interest (ROI)‐based functional connectivity. These findings support the theory that insomnia is linked to alterations in MTG function.…”
Section: Discussionmentioning
confidence: 99%